SPOTS: A Model for the Creation of Sustainable, Population-Based, Occupational Therapy Fieldwork Sites. Issue 1 (2nd January 2018) - Precin, Pat; Koenig, Virginia E.; Chiariello, Elizabeth; Masotti, Gabriela K.; Diamond, Bari N.; Lashinsky, Diana B.; Tierno, Olivia
ABSTRACT: This paper describes a model for the creation of sustainable, population-based, occupational therapy fieldwork sites (SPOTS). An example of a population-based fieldwork site was created with Appalachian Mountain People in Kentucky and its outcomes are presented. Outcomes were gathered using a wide variety of evaluation feedback forms. The results indicate that all staff, student, and college feedback were extremely favorable as detailed and suggest that others may use the SPOTS Model to develop population-based occupational therapy services that address public health issues for people with disabilities identified in Healthy People 2020 and create scholarly opportunities for students and faculty.